Application of online and offline blended teaching model combined with curriculum ideological and political education: Taking the course of clinical anesthesiology for example (线上线下混合式教学融入课程思政在临床麻醉学教学中的应用) - LI Jing (李静); FAN Xiaoying (范晓英); ZHANG Wanping (张万平); SU Yuqiang (苏玉强) (Association of Integrative Nursing, 2023)
Anesthesiology is a subject which combines basic medicine and clinical medicine. It is a comprehensive medical subject that covers a wide range of clinical medicine and involves multiple disciplines. A qualified anesthesiologist should not only have a solid theoretical and practical foundation, but also have a good professional ethics, humanistic quality and social responsibility. Contemporary medical education organically integrates theoretical education with ideological and political education, which is an effective way to realize the fundamental task of cultivating morality and human beings. With the arrival of the "Internet + era", medical educators have been exploring the teaching road of how to give better play to the advantages of the Internet, make use of the Internet to make the connection between teachers and students closer, and try their best to improve and innovate the teaching of clinical anesthesiology. In this regard, after a comprehensive analysis of the current situation of clinical anesthesiology teaching, the group characteristics of contemporary college students and the characteristics of online-offline mixed teaching, the author explores the application of online-offline mixed teaching into curriculum ideology and politics in the course of clinical anesthesiology, aiming at improving the teaching effect and achieving the goal of cultivating virtues and cultivating people. (麻醉学专业是一门基础医学与临床医学密切结合的学科, 是临床医学中覆盖广泛、涉及多门学科的综合医学学科。合格的麻醉医生不仅要有扎实的理论及实践基础, 还需要有良好职业道德、人文素养和社会责任感。当代医学教育将理论教育和思想政治教育工作有机的融合, 是实现立德树人根本任务的有效途径。随着"互联网+时代"的到来, 如何更好地发挥互联网的优势, 利用互联网将师生之间的联系更加紧密, 全力改进和创新临床麻醉学的教学工作, 是医学教育工作者一直在探索的教学之路。本文在综合分析当前临床麻醉学教学现状, 当代大学生的群体特点及线上线下混合式教学特点后, 探索线上线下混合式教学融入课程思政在临床麻醉学教学中的应用, 旨在提升教学效果, 实现立德树人的目标。)